Thermodynamics-based finite strain viscoelastic-viscoplastic model coupled with damage for asphalt material. (15th December 2017) - Chen, F.; Balieu, R.; Kringos, N.
Highlights: A thermodynamics-based model under the finite strain framework is proposed. Thermo-viscoelastic-viscoplastic behaviors coupled with damage are well predicted. The response difference between in tension and in compression is captured. Permanent deformation damage of a practical pavement structure is simulated. Abstract: A thermodynamics based thermo-viscoelastic-viscoplastic model coupled with damage using the finite strain framework suitable for asphalt material is proposed in this paper. A detailed procedure for model calibration and validation is presented, utilizing a set of experimental measurements such as creep-recovery, constant creep, and repeated creep-recovery tests under different loading conditions. The calibrated constitutive model is able to predict the sophisticated time- and temperature- dependent responses of asphalt material, both in tension and in compression. Moreover, a scenario case study on permanent deformation (rutting) prediction of a practical asphalt pavement structure is presented in this work. This paper presents the main features of this new constitutive model for asphalt: (1) A thermodynamics-based framework developed in the large strain context to derive the specific viscoelastic, viscoplastic and damage constitutive equations; (2) A viscoelastic dissipation potential involving deviatoric and volumetric parts, in which Prony series representations of the Lamé constants are used; (3) A modified Perzyna's type viscoplastic formulation with non-associated flow rule adopted to simulate the inelastic deformation, using a Drucker–Prager type plastic dissipation potential; (4) A specific damage model developed for capturing the evolution disparity between tension and compression. As such, the developed model presents a robust, fully coupled and validated constitutive framework that includes the major behavioral components of asphalt materials, enabling thus an optimized simulation of predicted performance under various conditions. Further development improvements to the model in continued research efforts can be to include further environmental and physico-chemical material behavior such as ageing, healing or moisture induced damage.